The power of the between : an anthropological odyssey - Stoller, Paul (University of Chicago Press, 2009)
It is the anthropologist's fate to always be between things: countries, languages, cultures, even realities. But rather than lament this, anthropologist Paul Stoller here celebrates the creative power of the between, showing how it can transform us, changing our conceptions of who we are, what we know, and how we live in the world. Beginning with his early days with the Peace Corps in Africa and culminating with a recent bout with cancer, The Power of the Between is an evocative account of the circuitous path Stoller's life has taken, offering a fascinating depiction of how a career is shaped.